Gender and age features of fatty acid composition of blood plasma in mountain dwellers of transcarpathian region - Kedyk, Antonina; Rishko, Mykola (ScienceRise: Medical Science, 2018)
The aim of the work is to identify the age and gender characteristics of the fatty acid plasma spectrum in the inhabitants of the mountain settlements of the Transcarpathian region, depending on the body mass index. The object of the study is the lipid and fatty acid plasma spectrum. The subject of the study is the relationship between the state of the fatty acid composition of the plasma and the age and sex of the subjects. Materials and methods 54 inhabitants of the mountain village Vydrychka of Rakhiv district of Transcarpathian region (average altitude 797 m above sea level) were surveyed. The analysis of the fatty acid plasma spectrum was done, using the method of gas chromatography method, and also lipid spectrum was analyses and evaluation of the body mass index and abdominal circumference was done. Results: Inhabitants of mountain settlements over 40 years have significantly higher BMI, larger abdominal circumference, higher total cholesterol, higher levels of pentadecanoic, palmitic and stearic, oleic and linoleic acids, higher total polyunsaturated fatty acids (PUFAs), first of all because of a higher level of ώ6 PUFA. Similar deviations were also found among highlanders with overweight and 1st degree obesity, although they have a higher level of not only total but also individual ώ6 PUFAs, in particular, linoleic, Y-linolenic, ώ6-digomo-γ-linolenic, ώ6-arachidonic and ώ6-andrenic PUFA. Conclusions. People living in mountain settlements over 40 years old, overweight or obese have a higher level of total cholesterol and a more prognostically unfavorable profile of fatty acids due to higher levels of saturated fatty acids (pentadecane, palmitic and stearic fatty acids) and a higher level of total ώ6 PUFA. Favorable lipid and fatty acid profiles were found in persons younger than 40 years old and in subjects with normal weight. Significant differences in the composition of fatty acids among men and women were not found